Trends in Polarisation in Pakistan (The Pakistan Development Review, 2008)
This study analyses the trends in polarisation in Pakistan, in its rural and urban segments and its provinces, at the micro level during the period 1992-93 to 2001-02. Estimations are made by using the Bossert-Schworm measure (2006). The study finds fluctuating trends. In general, polarisation declined in all regions of Pakistan during 1996-97 and 2001-02, while 1998-99 is the period of maximum polarisation. Incorporating the household size reduces the extent of polarisation, implying that ignoring the household size overestimates polarisation. The comparison of trends in polarisation and income inequality shows that generally the trends in inequality and polarisation are similar.